Transcriptome analysis provides insights into the response of Lotus corniculatus roots to low-phosphorus stress - Zhao, Xin; Chen, Ke-ke; Wang, Lei-ting; Zhao, Li-Li; Wang, Pu-Chang (Frontiers in Plant Science, 2023)
Introduction A lack of soil phosphorus (P) is a principal factor restricting the normal growth of Lotus corniculatus in the karst area of Guizhou Province, China, but the response mechanism of L. corniculatus under low-phosphorus stress remains unclear. Methods Therefore, we treated two selected L. corniculatus lines (low-P-intolerant line 08518 and low-P-tolerant line 01549) from 13 L. corniculatus lines with normal phosphorus (0.5 mmol/L KH2PO4, NP) and low phosphorus (0.005 mmol/L KH2PO4, LP) concentrations to study changes in morphological, physiological and transcriptome data under low-phosphorus stress. Results The low-P-tolerant line 01549 exhibited better performance under low-phosphorus stress. Compared with the NP treatment, all root morphological indicators of the low-P-tolerant line 01549 increased, and those of the low-P-intolerant line 08518 decreased under low-P stress. Compared with the NP treatment, acid phosphatase (ACP), catalase (CAT), superoxide dismutase (SOD), and peroxidase (POD) activities, and the malondialdehyde (MDA), soluble sugar (SS), soluble protein (SP) and proline (Pro) contents of the two L. corniculatus lines increased under low-P stress. A transcriptome analysis of L. corniculatus showed that a total of 656 and 2243 differentially expressed genes (DEGs) were identified in line 01549 and line 08518, respectively. Meanwhile, the main pathways, such as carbohydrate metabolism, acid phosphatases, phosphate transporters and biosynthesis of secondary metabolites, as well as related genes were also screened by performing a KEGG enrichment analysis. Discussion The findings provide an essential point of reference for studying the physiological and molecular mechanism of the response to low-P stress in L. corniculatus.